Artetherapy in Jung and its therapeutic potential as a humanized intervention strategy in the school context of young people in high school (Research, Society and Development, 2022)
This work aims to seek the foundations of art therapy in Jung, in order to support its potential as a humanized intervention strategy in the school context of high school youth. This is characterized as bibliographical and documentary research, with a qualitative methodological approach. Jung was one of the main representatives of art therapy in the world and, therefore, he is the basis for this study. He was the creator of analytical psychology and developed the concept of art therapy and many of the principles of this technique in his clinical practice from 1920 onwards. His considerations influenced scholars worldwide, such as Nise da Silveira (Brazil) and Margareth Naumburg (North-American). For Jung, the symbols present in the individual and collective unconscious were manifested in art. And, through this, the therapist can travel a beautiful path of unveiling with the patient, helping him in the difficult task of interpretation from the perspective of integrating his Self and his environment. Art therapy, and at no time was proposed by Jung, should be restricted to the clinic. In this sense, there is a rich and wide range of contents and techniques that can be applied for therapeutic purposes in many contexts. Education is one of them! The Common National Curriculum Base (2018) realizes that art should be part of the education of children and young people, from basic education to high school. The school, therefore, using art in education, can become a support tool for the prevention and promotion of the mental health of young people in high school.